2015
DOI: 10.1163/15685411-00002926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed-gall nematode, Anguina tritici, on bread wheat grain characteristics and yields in Turkey

Abstract: The effects of Anguina tritici on wheat yields and agronomic components were investigated at Thrace Agricultural Research Institute, Turkey, during the 2013 and 2014 growing seasons. Evaluations during 2013 focused on the wheat cv. Pehlivan, which is widely cultivated in Turkey. In this cultivar, A. tritici led to a grain infection in infected spikes of 0-100%, with an average of 61.8%. In 2014, yield losses caused by A. tritici were investigated in four wheat cvs, Pehlivan, Selimiye, Gelibolu and Kate-A. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…In this regard, the possibility of yield reduction is attributed to the high population density of CCN attack root of tomato plants and impaired nutrient uptake and water absorption 83 . Also, wheat gall nematode causes significant yield losses and affects grain quantity and quality 84 . Moreover, Snider et al 85 concluded that, the yield reductions are the result of anatomical and physiological changes that occur in the cotton root system as the nematode progresses through its lifecycle.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the possibility of yield reduction is attributed to the high population density of CCN attack root of tomato plants and impaired nutrient uptake and water absorption 83 . Also, wheat gall nematode causes significant yield losses and affects grain quantity and quality 84 . Moreover, Snider et al 85 concluded that, the yield reductions are the result of anatomical and physiological changes that occur in the cotton root system as the nematode progresses through its lifecycle.…”
Section: Discussionmentioning
confidence: 99%
“…Root-lesion nematodes are documented to cause in the range of 10 to 85% yield loss on wheat crop (Nicol & Rivoal, 2008;Smiley, 2010). Also, other losses of wheat are caused by the seed gall nematode (Anguina tritici), stem and bulb nematode (Ditylenchus dipsaci) (Tulek et al, 2015) and root-knot nematodes (Meloidogyne spp.) (Seid et al, 2015).…”
Section: Major Plant-parasitic Nematodes Of Wheatmentioning
confidence: 99%
“…• Distribution: The distribution pattern of seed gall nematode has been reported in West Africa, North Africa, Australia, Brazil, China, India, Turkey, France, Italy, Iraq, USA (Tulek et al, 2015). According to latest classification altogether there are 11 species of Anguina (Powers et al, 2001).…”
Section: Sting Nematodementioning
confidence: 99%